2008
DOI: 10.1177/000313480807400318
|View full text |Cite
|
Sign up to set email alerts
|

Are Adrenal Injuries Predictive of Adrenal Insufficiency in Patients Sustaining Blunt Trauma?

Abstract: Adrenal insufficiency (AI) is an uncommon life-threatening development in trauma patients. The aim of this study was to determine if adrenal injury sustained during blunt trauma is associated with an increased risk of AI. A single-institution retrospective cohort review was performed over a 3-year period on all patients with blunt trauma requiring intensive care admission and mechanical ventilation for longer than 24 hours. Adrenal injuries were identified on admission CT scan. All patients with AI were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…The interesting point in this study is that cosyntropin test showed cortisol levels higher than classic hypo-adrenal states so the authors concluded a functional hypoadrenalsim in these multisystem critically ill patients rather than true hypoadrenalism state [39]. So no benefit from pharmacologic cortisol doses but physiologic doses of cortisol could be beneficial [32].…”
Section: Managementmentioning
confidence: 96%
See 2 more Smart Citations
“…The interesting point in this study is that cosyntropin test showed cortisol levels higher than classic hypo-adrenal states so the authors concluded a functional hypoadrenalsim in these multisystem critically ill patients rather than true hypoadrenalism state [39]. So no benefit from pharmacologic cortisol doses but physiologic doses of cortisol could be beneficial [32].…”
Section: Managementmentioning
confidence: 96%
“…This entity is known in the literature as functional adrenal insufficiency. During severe illness about 24% of cases has decreased cortisol levels [32]. The underlying mechanism is not fully understood but there are some possibilities:-The effect of cytokines and inflammatory mediators on the hypothalamus-pituitary-adrenal system This hypothesis is supported by animal studies that showed role for IL-6 on the HPA.…”
Section: Pseudohypoadrenalismmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Other causes of adrenal necrosis include emboli, sepsis, and blunt trauma. 6,7 Other causes of adrenal crisis are listed in Table 3.…”
Section: Adrenal Crisismentioning
confidence: 99%
“…Adrenal hematomas per se have also been reported to be associated with higher injury severity and mortality compared to non-adrenal gland trauma. The exact cause of the higher mortality and morbidity associated with adrenal gland trauma is unknown but adrenal insufficiency has been hypothesized to play some role [ 9 , 11 , 17 19 ]. The clinical significance of bilateral adrenal hematoma remains even more unknown due to the relative rarity of bilateral adrenal hematomas and the insufficient number of cases with bilateral adrenal hematomas among patients with adrenal injuries.…”
Section: Introductionmentioning
confidence: 99%